Transformed Structural Properties Method to Determine the Controllability and Observability of Robots - Dany Ivan Martinez; José de Jesús Rubio; Victor Garcia; Tomas Miguel Vargas; Marco Antonio Islas; Jaime Pacheco; Guadalupe Juliana Gutierrez; Jesus Alberto Meda-Campaña; Dante Mujica-Vargas; Carlos Aguilar-Ibañez (Applied Sciences, 2021)
Many investigations use a linearization method, and others use a structural properties method to determine the controllability and observability of robots. In this study, we propose a transformed structural properties method to determine the controllability and observability of robots, which is the combination of the linearization and the structural properties methods. The proposed method uses a transformation in the robot model to obtain a linear robot model with the gravity terms and uses the linearization of the gravity terms to obtain the linear robot model; this linear robot model is used to determine controllability and observability. The described combination evades the structural conditions requirement and decreases the approximation error. The proposed method is better than previous methods because the proposed method can obtain more precise controllability and observability results. The modified structural properties method is compared with the linearization method to determine the controllability and observability of three robots.